Kepemimpinan Visioner Kepala Sekolah Dalam Mewujudkan Pendidikan Berbasis Masa Depan - Ilhami, Azhar Hari; Fathoni, Tamrin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study examines the role of visionary leadership in improving the quality of education at MA Ma’arif Balong. The findings indicate that the school principal has successfully established a clear and inspiring vision that focuses not only on academic achievement but also on character development and 21st-century skills. This vision provides direction for teachers and students, making the learning process more effective and goal-oriented. Additionally, transformational leadership is implemented by involving various stakeholders, including teachers, staff, and parents, in decision-making and policy implementation. This involvement fosters a sense of ownership and collective commitment to the school’s vision. Furthermore, the principal promotes innovation in learning by integrating technology and adopting Project-Based Learning (PBL), despite limited resources. This strategy enhances technology-based learning and improves students' practical skills. Lastly, professional development programs, including training and workshops, have positively impacted teaching quality. These initiatives equip teachers with modern pedagogical approaches that align with technological advancements. Overall, the visionary leadership at MA Ma’arif Balong has contributed significantly to creating a more adaptive and innovative educational environment. The study highlights that visionary and transformational leadership are crucial factors in preparing schools to face the challenges of the digital era.